Water exchange rates and mechanisms in tetrahedral [Be(H2O)4]2+ and [Li(H2O)4]+ complexes using DFT methods and cluster‐continuum models. Issue 19 (28th June 2016) - Regueiro‐Figueroa, Martín; Esteban‐Gómez, David; Pujales‐Paradela, Rosa; Caneda‐Martínez, Laura; de Blas, Andrés; Platas‐Iglesias, Carlos
Abstract: The water exchange reactions in aquated Li + and Be 2+ ions were investigated with density functional theory calculations performed using the [Li(H2 O)4 ] + ·14H2 O and [Be(H2 O)4 ] 2+ ·8H2 O systems and a cluster‐continuum approach. A range of commonly used functionals predict water exchange rates several orders of magnitude lower than the experimental ones. This effect is attributed to the overstabilization of coordination number four by these functionals with respect to the five‐coordinated transition states responsible for the associative (A ) or associative interchange (Ia ) water exchange mechanisms. However, the M06 and M062X functionals provide results in good agreement with the experimental data: M062X/TZVP calculations yield a concertedIa mechanism for the water exchange in [Be(H2 O)4 ] 2+ ·8H2 O that gives an average residence time of water molecules in the first coordination sphere of 260 μs. For [Li(H2 O)4 ] + ·14H2 O the water exchange reaction is predicted to follow anA mechanism with a residence time of inner‐sphere water molecules of 25 ps. Abstract : DFT calculations using cluster‐continuum models provide a detailed picture of the water exchange mechanism in [Be(H2 O)4 ] 2+ and [Li(H2 O)4 ] 2+ at the molecular level and activation parameters in excellent agreement with experimental data.